Formulasi Edible Film Ekstrak Daun Sirih (Piper betle L.) sebagai Antihalitosis - MOCH FUTUCHUL ARIFIN; LILIEK NUR HIDAYATI; SYARMALINA SYARMALINA; RENSY RENSY (Fakultas Farmasi Universitas Pancasila, 2010)
Halitosis (bad breath) is the most complained problem among mouth and teeth health. The source of halitosis are volatile sulfur compounds produced by Streptococcus mutans from degradation of food debris. Sirih leaves (Pqaer betle L.) are traditionally used as mouth antiseptic for its volatile oil. The aim of this research was to formulate sirih extract into an edible film. The leaves were macerated with 96% ethanol for 24 hours, resulting to an extract with minimum inhibitory concentration (MIC) on Streptococcus mutans of 8.49x10-3 g/ml. The extract with strength quadruple of the MIC, or equal to 0.92% povidone iodine, was formulated using 23 factorial design. Com starch, hydroxypropyl methylcellulose (HPMC) and sorbitol were independent variables and drying time, moisture, hlm thickness, disintegrating time, and iilrn strength were the dependent ones. The results showed that HPMC significantly fastened the drying time, decreased the moisture, and lengthened the disintegrating time. Sorbitol significantly lengthened the drying time, increased the moisture, and strengthened the film, while corn starch decreased the moisture and lengthened the disintegrating time. Optimation of the formula ingredients using contour plot superimposed cannot be determined due to edible film disintegrating time that was out of comparative interval.